Daughter from a wishing tree: unusual tales about women in mythology - Murty, Sudha (Gurugram; Puffin Books, 2019)
The women in Indian mythology might be fewer in number, but their stories of strength and mystery in the pages of ancient texts and epics are many. They slayed demons and protected their devotees fiercely. From Parvati to Ashokasundari and from Bhamati to Mandodari, this collection features enchanting and fearless women who frequently led wars on behalf of the gods, were the backbone of their families and makers of their own destinies.
Keywords: Women--Mythology; Hindu women; Children's Fiction